Implikasi Kebijakan Merge Bank Syariah Indonesia terhadap Pertumbuhan Ekonomi - Syamsarina, Syamsarina; Yusuf, Muhamad (Fakultas Syariah IAIN Kerinci, 2022)
This article aims to highlight the opportunities and challenges of Islamic banking in Indonesia after the merger and the implications for national economic growth from the perspective of Islamic banking. This study uses a descriptive analytical method which is literary in nature. The source of law in question is in the form of primary data in the form of laws and regulations and other sources of law. In addition, the secondary data of this study came from various literature such as books, scientific articles and other literature related to the object of research. The data analysis technique is carried out through several stages, namely focusing on data, presenting data, and drawing conclusions. The results of the research show that the formation of BSI through indeed creates various opportunities, one of which is the number of capital aspects becomes larger which will affect other aspects. Such as, Islamic financial literacy and inclusion funds are getting bigger, the market penetration network is getting wider, the creation of financial products that are increasingly diverse and low-cost and can take part to help finance strategic projects that can help grow the national economy